Voices of parents, guardians and/or caregivers of children under six years in relation to the use of screens during the pandemic and post-pandemic. Qualitative study - Ribeiro, María A.; Castillo, Emanuel L.; Lardies Arenas, Fernanda M.; Velázquez, María C.; García, Sandra V.; Dias de Carvalho, Tatiana (Revista del Hospital Italiano de Buenos Aires, 2024)
Objective: to know the voices of parents, guardians and/or caregivers of children under six years of age who reside in the Buenos Aires Metropolitan Area (AMBA), in relation to their use of screens, during the pandemic and post-pandemic period.Materials and methods: exploratory study, with a qualitative approach. Responses to an open question “Would you like to add any comments about something we haven't asked?” of a voluntary and anonymous online survey, which was aimed at relatives of children under six years of age. The process of analyzing the narratives coming from the responses was carried out through content analysis, which was organized in two stages: exploration and classification of the material and treatment of the results obtained and their interpretation.Results: 72 people responded to the question during the pandemic and 88 during the post-pandemic period. Benefits and usefulness were considered positive aspects. Risks and consequences for development, negative in both periods. As for reflections, the narratives vary from awareness of technology in their children's lives to a certain guilt for using these resources in their upbringing.Conclusion: the results demonstrate positive and negative aspects, such as its use for education and the risks for psychomotor and cognitive development, respectively. Regarding the reflections, they were observed from a certain guilt for using these resources in raising their children to the awareness of the importance of technology in the current reality.
Keywords: screen time; children; COVID-19; parents; caregivers; qualitative analysis